Cyberbullying as an associated factor to psychological distress and suicidal ideation in Mexican schooled adolescents - Domínguez Mora, Raquel; Vargas Jiménez, Esperanza; Castro Castañeda, Remberto; Medina Centeno, Raúl; Huerta Zúñiga, Claudia Gregoria (Acta Universitaria, 2019)
The aim of this article is to examine the influence of cyberbullying behavior on psychological distress and suicidal ideation in terms of gender, in Mexican school-age adolescents attending junior high school. Participants were 1676 adolescents, 53.9% women and 46.1% men, aged between 12 and 17 years (M = 13.65, SD = 1.14), selected through a proportional stratified sampling. 90.74% of adolescents are not cyberbullies and only 9.26% are cyberbullies. A higher prevalence of psychological distress and suicidal ideation was reported in both sexes when cyberbullying behaviors were manifested; however, overall women presented higher means of suicidal ideation and psychological distress. In conclusion, significant differences were observed in suicidal ideation and psychological distress in accordance with sex, as well as the degree of participation in cyberbullying behavior.